Climate, God and Uncertainty A transcendental naturalistic approach beyond Bruno Latour - Petersen, Arthur (UCL Press, 2023)
Climate, God and Uncertainty moves beyond Bruno Latour's thought to understand what climate change means for philosophical anthropology and wider culture. What are, for example, the philosophical implications of climate change and its associated uncertainties? Referring mainly to works by Latour, William James and Heinrich Rickert, Petersen develops 'transcendental naturalism' to reinterpret the interface between science and politics in the context of climate change. He highlights, for instance, issues such as the religious disenchantment of nature, the scientific disbelief in a plurality of value-laden perspectives, and the disregard for non-modern worldviews in politics. In developing its argument, the book makes a methodological intervention on the sort of naturalism that guides both Latour's work and a large part of the academic field called 'science and religion'. Praise for Climate, God and Uncertainty 'The challenges of a changing climate raise disturbing questions about being human in the world, ones that cannot adequately be answered through scientific inquiry. In this original interrogation and extension of the work of Bruno Latour, Petersen constructs a philosophical position that takes seriously the realities of a changing natural world, the human search to ground our sense of value, and the possibility of God. Climate, God and Uncertainty is an exciting new addition to the small, but growing, literature on climate change, religion and philosophy.' Mike Hulme, University of Cambridge 'This innovative and exciting work explores the rich potential of "transcendental naturalism" as a bridge between science and religion. Drawing on the work of William James, Heinrich Rickert and Bruno Latour, Petersen maps out a fresh approach that goes beyond current accounts of naturalism, opening up a deeply satisfying account of our engagement with the natural world.' Alister McGrath, Emeritus Andreos Idreos Professor of Science and Religion, University of Oxford 'How to live with the pervasive reality of uncertainty and a plurality of perspectives in science, religion and politics without playing down the sciences and our responsibilities? The "transcendental naturalism" Arthur Petersen articulates in this book respects science while leaving room for other elements: wonder, judgements and values, and the way we construct provisional models of reality. These issues are especially acute in the context of climate change, when we face the interplay of science and policy. Petersen stresses the importance of imagination to articulate meaning and of recognising a plurality of value-laden perspectives, striving for responsible action and sensitivity to that which may escape planning and policy. This book can be read fruitfully in at least two ways, as a highly relevant reflection on religion and science in the face of climate change and as a profound philosophical analysis of pluralism and provisionality, and hence of living with uncertainty.' Willem B. Drees, Professor Emeritus of Philosophy of Religion and Ethics, Leiden University and of Philosophy of the Humanities, Tilburg University